Territorio de coyotes, agroecosistemas y cambio tecnológico en una región cafetalera de Costa Rica - Picado Umaña, Wilson (2009)
This paper analyzes the technological change in a coffee growing region of Costa Rica, since the 1950?s to the present. Its objective is to identify the main social and agroecological consequences of the modernization process applied to the farming systems, in the Canton of Tarrazú, during the last fifty years. This study includes the use of a database of the 1955 Agricultural Census, the revision of agronomical documentation, interviews with producers, the analysis of different cartographic sources, and field work. We consider that this analysis points out the agrarian costs and several social contradictions associated to the technological modernization process